The FrogID dataset: expert-validated occurrence records of Australia’s frogs collected by citizen scientists - Jodi J.L. Rowley; Corey T. Callaghan (ZooKeys, 2020)
This dataset represents expert-validated occurrence records of calling frogs across Australia collected via the national citizen science project FrogID (http://www.frogid.net.au). FrogID relies on participants recording calling frogs using smartphone technology, after which point the frogs are identified by expert validators, resulting in a database of georeferenced frog species records. This dataset represents one full year of the project (10 November 2017–9 November 2018), including 54,864 records of 172 species, 71% of the known frog species in Australia. This is the first instalment of the dataset, and we anticipate providing updated datasets on an annual basis.